La utilización de las TICs para potenciar el aprendizaje significativo en el área de Ciencias Naturales en los estudiantes de sexto grado paralelo “A”, de la escuela de educación básica “Lauro Damerval Ayora Nº. 2” de la ciudad de Loja período lectivo 2014-2015 - Munive Riofrío, Viviana Verónica (2015)
This research project called: LA UTILIZACIÓN DE LAS TICs PARA POTENCIAR EL APRENDIZAJE SIGNIFICATIVO EN EL AREA DE CIENCIAS NATURALES EN LOS ESTUDIANTES DE SEXTO GRADO PARALELO A, DE LA ESCUELA DE EDUCACIÓN BÁSICA “LAURO DAMERVAL AYORA” No. 2 DE LA CIUDAD DE LOJA PERÍODO LECTIVO 2014-2015, he worked with the overall objective: To determine the use of ICTs to promote meaningful learning in the area of Natural Sciences students in sixth grade parallel sublevel of primary and secondary school education Basic LauroDamervalAyora No. 2 2014-2015, the same as was used for the development and implementation of strategies for teaching Natural Sciences; to carry out the research the following methods were used: Scientific; descriptive and analytic-synthetic, the same that were used throughout the research process, and, on the analysis of empirical data, also techniques such as survey, pretest and posttest for teachers and students that served them for information on the difficulties related to the issue were used; for the analysis and interpretation of statistical data and go elucidating the concerns disclosed, the population consisted of 18 children and a teacher; All the investigative work can say that the Education Unit does not have a computer center which prevents students take advantage of these technological tools to access knowledge and thus a significant learning that favors the acquisition of life skills and work that favor their integration into society of knowledge, and the role of teachers has changed significantly in the process of learning to use in the classroom since not know and apply these technological tools are not accessing the universality in education, equality in education, the practice of teaching and learning quality and professional development of teachers as well as management and administration more efficient management of the educational system, by which the curriculum is working by implementing strategies in the form of workshops and with the help of technological tools allowed the student has more elements (visual and auditory) to enrich the teaching-learning process